Effect of Physical Activity on Plasma PCSK9 in Subjects With High Risk for Type 2 Diabetes - Mäkelä, Kari Antero; Leppäluoto, Juhani; Jokelainen, Jari; Jämsä, Timo; Keinänen-Kiukaanniemi, Sirkka; Herzig, Karl-Heinz (Frontiers in Physiology, 2019)
Background: Proprotein convertase subtilisin-kexin type 9 (PCSK9) is a liver serine protease regulating LDL cholesterol metabolism. PCSK9 binds to LDL receptors and guides them to lysosomes for degradation, thus increasing the amount of circulating LDL cholesterol. The aim of the study was to measure the plasma PCSK9 concentrations in prediabetic subjects and the association to physical activity. Methods: 67 subjects from both gender with a high risk of type 2 diabetes was included to a randomized controlled trial with a 3-month physical activity intervention. Physical activity intensities and frequencies were monitored throughout the intervention using a portable accelerometer. The plasma was collected both before and after intervention for analyzation of PCSK9 and cardiovascular biomarkers. Results: Plasma PCSK9 did not relate to physical activity although number of steps were 46% higher in the intervention group than in the control group (p < 0.029). Total cholesterol was positively correlated with plasma PCSK9 (R=0.320, p=0.008), while maximal oxygen uptake was negatively associated (R=-0.252, p=0.044). After the physical activity intervention PCSK9 levels were even stronger inversely associated with maximal oxygen uptake (R=-0.410, p=0.0008) and positively correlated with HDL cholesterol (R=0.264, p=0.030). Interestingly, plasma PCSK9 levels were higher in April than in January. Conclusions: The achieved low physical activity by our subjects with high risk for type 2 diabetes did not influence plasma PCSK9 levels. Intervention with higher physical activities might be more effective in reducing PCSK9 levels.